Distribution of pathologic smear results and histopathologic agreement in precancerous cervical lesions - Eser Colak; Esra Zeynep Coskunoglu (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: The accuracy of the Papanicolau smear test is very important in cervical cancer which is preventable cancer. In this study, we aimed to investigate the distribution of smear results and cyto-histopathological correlation and agreement in biopsies.